2001
DOI: 10.1103/physrevb.63.134114
|View full text |Cite
|
Sign up to set email alerts
|

Thermal vacancy formation andD03ordering in nanocrystalline intermetallic(Fe3

Abstract: The correlation between thermal vacancy characteristics and D0 3 ordering in ball-milled nanocrystalline (Fe 3 Si) 95 Nb 5 was studied by combined measurements of x-ray diffraction and positron annihilation. Structural stabilization due to grain boundary segregation of Nb enables high-temperature positron lifetime measurements up to 1023 K from which vacancy formation parameters identical to those in single-crystalline D0 3 Fe 3 Si are deduced. Measurements of coincidence Doppler broadening show that prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…5 Chemically sensitive free volume studies of interfaces in nanocrystalline materials by means of Doppler broadening have been initiated recently. 6,7 The present work is a first systematic in-depth study exploring the potentials of this method for chemically sensitive characterization of free volumes in a structurally complex material which develops during the various states of solid-state amorphization.…”
Section: Introductionmentioning
confidence: 99%
“…5 Chemically sensitive free volume studies of interfaces in nanocrystalline materials by means of Doppler broadening have been initiated recently. 6,7 The present work is a first systematic in-depth study exploring the potentials of this method for chemically sensitive characterization of free volumes in a structurally complex material which develops during the various states of solid-state amorphization.…”
Section: Introductionmentioning
confidence: 99%
“…The transition rate  fg is understood to be proportional to D + , whose dependence on the temperature is given by If the diffusion length L + competes the size of the grain the probability of the transition rate from free to grain boundary is high. Pasquini et al [13] have shown that the trapping coefficient for the thermal vacancy shows an increasing trend as temperature rises. Further, the trapping rate is expected to be proportional to the thermal vacancy concentration.…”
Section: Resultsmentioning
confidence: 99%
“…The equation (12) has been used to obtain the mean positron lifetime in pure and doped ZnO thin films, while equation (13) has been used to calculate the S-parameter in these films.…”
Section: Formulation Of the Diffusion Trapping Modelmentioning
confidence: 99%
“…The formation of B2, L1 2 , and D0 3 order in several nanocrystalline alloys have been reported, including Ti-Al, Fe-Al, Fe-Si, Fe-Co, Ni-Al, and Cu-Au, sometimes with ternary additions. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] These studies have emphasized various aspects of defects and diffusion in nanostructured alloys, with comparisons to bulk materials. The reverse transformation, disordering a B2-ordered Fe 60 Al 40 nanocrystalline alloy during high-energy ball milling, has also been studied recently.…”
Section: Introductionmentioning
confidence: 99%
“…The reverse transformation, disordering a B2-ordered Fe 60 Al 40 nanocrystalline alloy during high-energy ball milling, has also been studied recently. 26 A number of features seem common to the reordering of chemically disordered nanocrystalline materials, in spite of differences in their methods of synthesis ͑e.g., ball milling, 10,11,15,[17][18][19][20]23,24,27 plastic deformation, 28 gas-phase condensation with compaction, 21,22 sputtering, 16 ion irradiation 29 ͒, microstructures ͑isolated clusters 16 or more typically micron-sized particles composed of nanometersized grains͒, and ordered structures. Reordering can occur at low temperatures, and involves only few jumps of nonequilibrium vacancies that were not promptly annihilated at sinks.…”
Section: Introductionmentioning
confidence: 99%